The Constitutional Court in the Face of the Legislative Authority in Algeria - Rais, Samia (Journal of Legal Studies and Researches, 2024)
The main objective of the establishment of the Constitutional Court is to achieve the rule of law and lay its foundations, and this can only be done by subjecting all public authorities within the state to the authority of law, Including the legislative authority, which he subjected to the oversight of the Constitutional Court, whether upon inauguration, exercising activity, or in resolving its disputes with the rest of the authorities.